(untitled) (Docentes 2.0 Journal, 2023)
School is in charge of getting students to learn to have a harmonic coexistence in the society. However, the reality shows how difficult this task is for educators when facing the diversity of the whole school community. This fact makes that educators prefer the homogenization of all processes instead of attending that diversity. In this way, it is necessary to analyze the role of the school in the transformation that is needed to create participative and democratic environments where others are recognized from his diversity as an individual or as a group, taking into account the research literature review that there is on the field. This analisis let us give proof of the challenges education has to comprehend diversity as a key element for the school coexistence which contributes to make the school be a space of colective construction where different is understood as something inherent of human kind.